1989
DOI: 10.1002/pd.1970090502
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exsanguination following intrauterine angiographic assessment and selective termination of a hydrocephalic, monozygotic co‐twin

Abstract: Selective termination by intracardiac potassium chloride injection was performed in twins discordant for hydrocephaly at 20 weeks' gestation. Because of the potential for vascular anastomoses to exist between the twins, fetal angiography was performed prior to the selective termination procedure. Determination of vascular connections between the fetuses was hindered by fetal bradycardia following intracardiac administration of contrast material. Selective termination was performed without difficulty using intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This discrepancy can be explained only when the anastomoses are carefully delineated, and the circumstances of birth are known. This topic was especially well discussed in the case reports by Donnenfeld et al ( 1989 ) , and Bendon and Siddiqi ( 1989 The smaller twin was growth-restricted because of its velamentous insertion of the cord. This case does not represent a twin transfusion syndrome.…”
Section: Twin-to-twin Transfusion Syndromementioning
confidence: 94%
See 1 more Smart Citation
“…This discrepancy can be explained only when the anastomoses are carefully delineated, and the circumstances of birth are known. This topic was especially well discussed in the case reports by Donnenfeld et al ( 1989 ) , and Bendon and Siddiqi ( 1989 The smaller twin was growth-restricted because of its velamentous insertion of the cord. This case does not represent a twin transfusion syndrome.…”
Section: Twin-to-twin Transfusion Syndromementioning
confidence: 94%
“…They were nearly uniformly successful, but the possibility of destruction of the dividing membranes exists with this technique. Selective feticide can then be undertaken when fetal trisomy is diagnosed by any of these techniques (Kerenyi and Chitkara 1981 ;Chitkara et al 1989 ; see also Donnenfeld et al 1989 ) . Pijpers et al ( 1988 ) studied 83 pregnancies and obtained karyotypes of both twins in 77 cases (93%).…”
Section: Cytogenetics and "Heterokaryotypic Mz Twins"mentioning
confidence: 98%
“…The possibility of the development of DIC or exsanguination after the death of one twin in utero may have important implications in the treatment of the twin-to-twin transfusion syndrome or in cases of fetal anomalies by selective feticide of one twin. This has been practiced so as to allow the continuation of pregnancy for the other twin [11,42]. The possibility of serious fetal damage in the survivor as outlined above must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Larroche and her colleagues [26] suggested that in utero damage to the brain may result from acute hypotension. Donnenfeld et al [11] found that, after unsuccessful elective termination of a hydrocephalic twin with potassium chloride injection, the normal twin exsanguinated. Fusi et al [15] illustrated a monochorionic twin with acute exsanguination after fetal death.…”
Section: Outcome Of the Surviving Twinmentioning
confidence: 99%
“…In utero sampling has been done in only two published cases in addition to this one (Donnenfeld et al, 1989, Fusi et al, 1991. Neither found any clotting abnormality.…”
Section: **No Reference Range Availablementioning
confidence: 99%